4D Applications of GIS in Construction Management - A. Chaitanya Kumar; T. Reshma (Advances in Civil Engineering)
Construction industries broadly involve different set of construction activities which are to be executed as per schedule and the major software used for scheduling is PRIMAVERA and Microsoft Project (MSP). But the software still lacks a feature of providing spatial aspects of information in construction schedule. Recently, advanced technology like 4D GIS plays a major role in overcoming the limitation of the software. 4D GIS technology includes integration of 2D drawings from AutoCAD and schedules prepared in PRIMAVERA software. In the present study, a multistair residential building has been selected. ARCMAP 10.2 is used for interlinking of schedules as well as drawings and ARCSCENE has been used for developing 4D view. This linkage between scheduled activities and respective drawings in GIS helps in identifying construction sequences and also in detecting logical errors that occur in project schedules. The developed 4D view provides better visualization of construction progress of a project.